Pengembangan Modul Pembelajaran Tematik Berbasis Kegiatan Harian Untuk SD Kelas IV: Modul Pembelajaran Tematik Berbasis Kegiatan Harian - Diana Besni; Darmansyah Darmansyah; Ridwan Ridwan; Azwar Ananda (Journal of Pedagogy and Online Learning, 2022)
The changes of learning process in elementary school into thematic learning causes a lack of appropriate learning sources. In Curriculum 2013 (K13), students and teachers must have manual books. These books provide some general themes, but they do not reach every daily activity that suitable with student’s characteristics yet. Based on these cases above, in this development research, researcher will develop a valid, practical, and effective thematic learning module based daily activity for fourth grade student in elementary school. This is a development research use 4-D Model, namely define, design, and disseminate. The result of this development research is a valid, practical, and effective thematic learning module based daily activity. Based on research finding, researcher can conclude that (1) based on validity test, the content, construction, and language used in this thematic learning module based daily activity is valid, (2) the development process produces a valid, practical, and effective thematic learning module based daily activity in order to achieve learning outcomes so this learning module can be used in learning process.